Triplet‐Primed PCR Assays for Accurate Screening of FMR1 CGG Repeat Expansion and Genotype Verification. Issue 5 (24th May 2022) - Rajan‐Babu, Indhu‐Shree; Lian, Mulias; Chong, Samuel S.
Abstract: Fragile X syndrome and other fragile X‒associated disorders are caused by the full‐mutation (>200 copies) and premutation (55 to 200 copies) expansion, respectively, of the CGG short tandem repeat in the fragile X messenger ribonucleoprotein 1 ( FMR1 ) gene. Clinical diagnostic laboratories use Southern blot analysis and polymerase chain reaction (PCR)‐based tests to detect and/or size the FMR1 CGG repeats. The development of sensitive and high‐throughput triplet‐primed PCR (TP‐PCR) assays has diminished the need to subject all samples to Southern blot analysis, which is both labor‐ and time‐intensive. In this article, we describe two direct TP‐PCR (dTP‐PCR) assays for the detection of FMR1 CGG repeat expansions. We outline a protocol that is based on melting curve analysis of dTP‐PCR amplicons for a rapid and cost‐effective first‐tier screening and identification of individuals with premutation and full‐mutation expansions. We also describe a protocol that employs capillary electrophoresis to resolve the dTP‐PCR amplicon fragments and to estimate the repeat sizes of normal (5 to 44 copies), intermediate (45 to 54 copies), and premutation alleles, as well as to detect full mutations and determine the structure of the FMR1 alleles. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Direct triplet‐primed PCR master mix preparation and amplification of the FMR1 CGG repeat locus for melting curve analysis Basic Protocol 2 : Melting curve analysis of direct triplet‐primed PCR amplicons on the Rotor‐Gene Q MD × 5plex high‐resolution melt platform Alternate Protocol : Melting curve analysis of direct triplet‐primed PCR amplicons on the LightCycler 480 system Basic Protocol 3 : Generation of direct triplet‐primed PCR melting curve analysis profiles Basic Protocol 4 : Direct triplet‐primed PCR master mix preparation and amplification of the FMR1 CGG repeat locus for capillary electrophoresis Basic Protocol 5 : Generation of control FMR1 plasmids for direct triplet‐primed PCR melting curve analysis Basic Protocol 6 : Sanger sequencing assay to verify FMR1 CGG repeat size and structure of plasmid DNA controls